Critical Constructability Principles for Girder Bridge Construction in Malaysia - Ding, Chu Sheng; Hafez Salleh; Kho, Mei Ye (International Journal of Sustainable Construction Engineering and Technology, 2020)
Implementing constructability concepts in a project can bring many benefits such as reduced project cost & duration, enhanced project quality, and improved site management. There were numerous research on the constructability concept since its introduction in late 1970. However, there are limited studies that identified the critical constructability principles for infrastructure projects. This study identified the critical design stage constructability principles for girder type river bridge construction in Malaysia. Based on extensive literature review and unstructured interviews with the experts in bridge construction, 54 constructability principles were identified. Questionnaires were distributed to professional engineers and G6 & G7 contractors in Malaysia to rate the 54 constructability principles in term of their importance or impact in enhancing the constructability of bridge construction based on 5-point Likert scale. The received 143 responses were analysed using factor analysis which is a data reduction tool of SPSS. Varimax method of orthogonal approach was adopted for factor rotation. Factor analysis had helped to generate 11 principal components or critical constructability principles. Cronbach’s Alpha reliability test also indicated good reliability of the questionnaire scale. The identified critical constructability principles can provide guidelines to the construction practitioners at the design stage to enhance the performance of bridge construction.